2021
DOI: 10.47616/jamrems.v2i2.102
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Vaccine: Global Stock Market “Game Changer”

Abstract: This research is a conceptual paper that examines the impact of the presence of the Covid-19 vaccine on investor sentiment and the performance of the global stock market after being hit by high concerns due to the pandemic. The results showed that each stage of vaccine development received high appreciation from stock investors, especially after vaccine candidates passed clinical trials in humans. Investors' positive sentiment towards the vaccine program boosted stock market performance. However, the sentiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Regarding the impact of COVID-19 vaccinations on the forex market, the results listed in Table 4 exhibit strong correlations for all the studied countries, especially in Europe, where the dynamic correlations are very high. This finding confirms previous conclusions regarding the strong impact of the COVID-19 vaccine's development on most developed and emerging markets (Vierlboeck and Nilchiani, 2021;Hartono, 2021;Kucher et al, 2021;Chan et al, 2021). Our results also corroborate the findings of the few existing articles regarding the study of the COVID-19 vaccination campaign on financial markets.…”
supporting
confidence: 92%
“…Regarding the impact of COVID-19 vaccinations on the forex market, the results listed in Table 4 exhibit strong correlations for all the studied countries, especially in Europe, where the dynamic correlations are very high. This finding confirms previous conclusions regarding the strong impact of the COVID-19 vaccine's development on most developed and emerging markets (Vierlboeck and Nilchiani, 2021;Hartono, 2021;Kucher et al, 2021;Chan et al, 2021). Our results also corroborate the findings of the few existing articles regarding the study of the COVID-19 vaccination campaign on financial markets.…”
supporting
confidence: 92%
“…Besides, many studies prove that mass campaign about Covid-19 vaccines receives positive sentiments from investors. [23][24][25][26] Therefore, the approvals of Covid-19 vaccines lighted the hope of humanity and economic recovery, and this phenomenon is reflected in the stock market. 14,25 However, none of them consider the existence of cross-dependency and heterogeneity problems.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Similar to Rouatbi et al (2021) , this study also showed that the influence of vaccination on energy stocks of developed countries is more pronounced than that of emerging countries. Hartono (2021) examines the effect of the presence of a Covid-19 vaccine on investor sentiment and the performance of global stock markets after being hit by heightened concerns due to the pandemic. The results suggested that each stage of vaccine development receives high praise from stock investors, especially after vaccine candidates pass human clinical trials.…”
Section: Literature Reviewmentioning
confidence: 99%